Analysis Comparative Method Shari’a Compliant Asset Pricing Model - Bekti Wiji Lestari; Erma Setiawati; Noer Sasongko (Universitas Muhammadiyah Sorong, 2021)
The researcher's view of the CAPM model is not in accordance with the Islamic economy because there is an Rf element as an instrument that contains an interest element, so a modified model of CAPM based on sharia is introduced, namely SCAPM. This study aims to analyze the differences in the SCAPM method according to Tomkins & Karim (1987) SCAPM non Rf, Ashker (1987) SCAPMZ, Shaikh (2010) SCAPM NGDP, and Hanif (2011) SCAPMI. The sampling technique used was purposive sampling and obtained 19 samples. Data analysis used is the calculation of Mean Absolute Deviation (MAD), Mean Square Error (MSE), and the coefficient of determination. The results of the calculation of Mean Absolute Deviation (MAD) and Mean Square Error (MSE) explain that there are differences from the SCAPM models without risk free rate, SCAPMZ, SCAPM NGDP, and SCAPMI. Meanwhile, SCAPMI has the best explanatory power than the other four SCAPM models. It is recommended that Islamic and conventional investors use SCAPMZ modeling in predicting stock returns.